Observer-based reliable stabilization of uncertain linear systems subject to actuator faults, saturation, and bounded system disturbances - Fan, Jinhua; Zhang, Youmin; Zheng, Zhiqiang (ISA transactions, 2013)
A matrix inequality approach is proposed to reliably stabilize a class of uncertain linear systems subject to actuator faults, saturation, and bounded system disturbances. The system states are assumed immeasurable, and a classical observer is incorporated for observation to enable state-based feedback control. Both the stability and stabilization of the closed-loop system are discussed and the closed-loop domain of attraction is estimated by an ellipsoidal invariant set. The resultant stabilization conditions in the form of matrix inequalities enable simultaneous optimization of both the observer gain and the feedback controller gain, which is realized by converting the non-convex optimization problem to an unconstrained nonlinear programming problem. The effectiveness of proposed design techniques is demonstrated through a linearized model of F-18 HARV around an operating point. •An observer-based saturating actuator fault-tolerant controller is designed.•Matrix inequality conditions are proposed for system stability and stabilization.•Observer and feedback gains are simultaneously optimized by nonlinear programming.•The closed-loop domain of attraction is estimated by an ellipsoidal invariant set.•A linearized model of F-18 HARV is stabilized under total loss of thrust-vectoring capability.